2004
DOI: 10.1038/sj.npp.1300639
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine Modulates Glutamatergic Transmission in the Bed Nucleus of the Stria Terminalis

Abstract: The bed nucleus of the stria terminalis (BNST) and its adrenergic input are key components in stress-induced reinstatement and maintenance of drug use. Intra-BNST injections of either beta-adrenergic receptor (beta-AR) antagonists or alpha2-adrenergic receptor (alpha2-AR) agonists can inhibit footshock-induced reinstatement and maintenance of cocaine- and morphine-seeking. Using electrophysiological recording methods in an in vitro slice preparation from C57/Bl6j adult male mouse BNST, we have examined the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
139
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(142 citation statements)
references
References 29 publications
2
139
1
Order By: Relevance
“…Thus, we examined the effects of yohimbine and atipamezole on glutamatergic transmission in the dorsolateral (dl) BNST. We previously reported that the ␣ 2 -AR agonists clonidine and UK14,304 elicit an acute depression of glutamatergic transmission in this region (UK14,304, 41.7 ‫ע‬ 7.7% of baseline, P < 0.05) (Egli et al 2005). We have replicated these data and show a representative experiment for comparison (Fig.…”
Section: Effect Of Atipamezole On Cocaine Cpp Extinctionsupporting
confidence: 71%
See 1 more Smart Citation
“…Thus, we examined the effects of yohimbine and atipamezole on glutamatergic transmission in the dorsolateral (dl) BNST. We previously reported that the ␣ 2 -AR agonists clonidine and UK14,304 elicit an acute depression of glutamatergic transmission in this region (UK14,304, 41.7 ‫ע‬ 7.7% of baseline, P < 0.05) (Egli et al 2005). We have replicated these data and show a representative experiment for comparison (Fig.…”
Section: Effect Of Atipamezole On Cocaine Cpp Extinctionsupporting
confidence: 71%
“…7B). Further, while the effect of UK14,304 was absent in slices prepared from ␣ 2A -AR KO mice (Egli et al 2005), yohimbine still caused a decrease (42.6 ‫ע‬ 7.5% of baseline; t = 5.44, df = 5, P < 0.003) in glutamatergic transmission in the dlBNST of these mice (Fig. 7C).…”
Section: Effect Of Atipamezole On Cocaine Cpp Extinctionmentioning
confidence: 99%
“…Reciprocal catecholamine signaling has interesting implications in the context of the aversive stimulus of drug withdrawal, due to norepinephrine's possible influence on dopaminergic signaling. Glutamatergic inputs from the vBNST exert strong excitatory influence over VTA dopamine neurons (Georges and Aston-Jones, 2002), and norepinephrine's actions through α 2A receptors decrease excitatory transmission in the vBNST (Egli et al, 2004). Moreover, during acute opiate withdrawal, norepinephrine can act through β-receptors to increase GABA A inhibition of VTAprojecting BNST neurons (Dumont and Williams, 2004), leading to increased inhibition of the VTA.…”
Section: Discussionmentioning
confidence: 99%
“…Recording electrodes of approximately 1 MO resistance were pulled on a Flaming/Brown microelectrode puller (Sutter Instruments, Novato, CA) and filled with ACSF. A bipolar Nichrome (A-M Systems, Carlsborg, WA) stimulating electrode was placed dorsally to the recording electrode within the dlBNST such that stimulation of the field resulted in two distinguishable negative shifts in potential: N1 (the TTX sensitive fiber volley estimate) and N2 (CNQX sensitive synaptic response) as previously reported (Weitlauf et al, 2004;Egli et al, 2005;Grueter and Winder, 2005). The amplitude (voltage) of the N2 was measured at a stimulation intensity that resulted in a voltage approximately 50% of the maximum N2 response.…”
Section: Field Potential Recordingsmentioning
confidence: 99%
“…Moreover, blockade of excitatory transmission within this same region also disrupts anxiety-related behavior (Walker and Davis, 1997). Due to these observations, our group characterized NE modulation of glutamatergic signaling in the dorsal and ventral lBNST (dlBNST, vlBNST), focusing on a 2 -and b-AR signaling (Egli et al, 2005). Studies, however, have also suggested a role for a 1 -ARs in the BNST, demonstrating that blocking a 1 -ARs decreases anxiety responses concurrent with reductions in hypothalamicpituitary-adrenal (HPA) axis activation (Cecchi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%